NP001 regulation of macrophage activation markers in ALS: A phase I clinical and biomarker study. Issue 7 (December 2014) - Miller, Robert G.; Zhang, Rongzhen; Block, Gilbert; Katz, Jonathan; Barohn, Richard; Kasarskis, Edward; Forshew, Dallas; Gopalakrishnan, Vidhya; McGrath, Michael S.
Abstract This is a phase I, placebo-controlled, single ascending dose safety and tolerability study of NP001 in patients with ALS. NP001 is a novel regulator of inflammatory macrophages and monocytes. As ALS progression is thought to be related to neuroinflammation, an additional objective of the study was to assess the effects of NP001 administration on monocyte activation markers. Thirty-two ALS patients were enrolled and received either placebo (eight) or one of four (six at each dose) ascending single i.v. doses (0.2, 0.8, 1.6 and 3.2 mg/kg NP001). Patients were monitored for safety, and blood monocyte immune activation markers CD16 and HLA-DR were assessed pre- and 24 h post-dosing. Changes from baseline were calculated. Results showed that NP001 was generally safe and well tolerated. Importantly, a single dose of NP001 caused a dose-dependent reduction in expression of monocyte CD16, a marker of monocyte activation/inflammation. Additionally, monocyte HLA-DR expression was also decreased in those patients with elevated values at baseline. In conclusion, these data indicate that NP001 has an acute effect on inflammatory monocytes in ALS patient blood. The potential for modulation of inflammation in the context of ALS disease progression will require further study with long-term follow-up.